PENERAPAN PEMBELAJARAN SEMI RISET UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA TENTANG SIFAT-SIFAT BAHAN TEKNIK PADA PEMBELAJARAN BAHAN TEKNIK DASAR - Tiwan Tiwan; Arianto Leman S (Faculty of Engineering, Universitas Negeri Yogyakarta, 2013)
ABSTRACTThe purposes of the research are to review the application strategies of semi-research learning on the students’ understanding of the characteristics of engineering materials and to reveal the role of the students. Also, to determine whether there was any significant difference on the students’ understanding whowere taught by using semi-research learning compared to the conventional one. The research method was quasi-experimental model with parallel or equivalent group, the experimental group and the control group. Each group got pretest before and posttest after the treatment. The study was conducted in Mechanical Engineering Department, Faculty of Engineering, Yogyakarta State University from September till November 2012 among 160 students of the first semester in academic year of 2012-2013. This study was using cluster sampling method by taking one class as control group and one class for experimental group. Data analysis techniques were using descriptive analysis and T-Test. Semi-research learning for the understanding on the characteristics of engineering materials can be conducted through the students’ research assignment. The students were given chance to review based on the literature and to prove through their autonomous research. After they completed their research process, they were asked to have presentation while the lecturer role as the facilitator. Most of the students were glad with this strategy because it made them as active learner to search, explore, prove and utilize their review. This learning model demanded the students to be active, independent, serious, and able to work together, to solve problems based on facts as well as scientific evidence. Also, there was significant difference on the students’ understanding of the characteristics of engineering materials, who were taught by using semi-research compared to the conventional method with the score of mean difference of 10 from 0-70 scale. Similarly, there was a difference from the mean improvement of 10 points. Keywords: Semi-research,students’ understanding of nature of engineering materials